The Role of the Patient's Family in Implementing the Discipline of Health Protocols at the Otanaha Hospital, Gorontalo City - Sabirin B. Syukur; Rini Asnawati; Serla Nusi; Mukti Ali Mokoginta; Nurhikma Fatmala Sulasni (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
The role of the community in each phase is needed to avoid more transmission. Efforts that can be made in the prevention phase by each individual include: wearing a mask, using a hand sanitizer/disinfectant, washing hands with soap and running water, keeping a distance of at least 1-2 meters from other people when outside the house. The purpose of this community service is to provide counseling to the community in the poly room of the Otanaha Hospital, Gorontalo City about the role of the patient's family in implementing health protocol discipline during the Covid-19 pandemic. Counseling was carried out through the pretest and posttest stages by distributing questionnaires to the public. There were 20 communities who were given counseling. The pre-test values ​​of knowledge about health protocol disciplines before counseling were obtained were Good 20%, Enough 15% and Less 65%, while after the counseling the post-test scores were found to be Good 55%, Enough 45%. Based on the results obtained that public knowledge about the role of the patient's family in implementing health protocol discipline has increased after being given counseling